(untitled) (Journal of Shaheed Suhrawardy Medical College, 2019)
Haemophilia A is an X linked disorder characterized by bleeding manifestations due to deficiency of factor VIII. Administration of factor VIII is the mainstay of treatment in case of bleeding which is very costly. That’s why fresh frozen plasma is a very good alternative in the management of mild to moderate bleeding. Here we present a case of 50 years old male presented to us with traumatic scrotal haematoma who was newly diagnosed with Haemophilia A. As the patient was unable to bear the cost of factor VIII, we managed the patient by transfusing fresh frozen plasma. After raising his activity of factor VIII up to 30% which was adequate for soft tissue trauma, surgical exploration of scrotum was done. Both the testes were found viable. Evacuation of clot was done followed by secondary closure of the wound J Shaheed Suhrawardy Med Coll, December 2018, Vol.10(2); 118-121